Microstructure, oxidation & mechanical properties of as-sprayed and annealed HVOF & VPS CoNiCrAIY coatings - Saeidi, Saman (2011)
Three HVOF and a VPS CoNiCrAlY coating were sprayed using Praxair CO-210-24 and Sulzer Metco Amdry 9951 powders. All coatings were subject to vacuum annealing treatments at different temperatures for different exposure times in order to achieve equilibrium microstructures in all test samples. Both HVOF and VPS, as sprayed and heat treated coatings were oxidised at 850°C and 1100°C for periods of up to 250 hours. Scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), transmission electron microscopy (TEM), X-ray diffraction (XRD) and laser diffraction powder size analyses were used in order to analyse the powder particle size distribution and characterise the microstructure of the as-received powders, as-sprayed coatings and annealed and oxidised coatings. Thermogravimetric analysis (TGA) was carried out on as-sprayed and heat treated HVOF and VPS coatings at 1100°C for 96 hours in order to compare the oxidation rate of HVOF and VPS coatings and investigate the effect of microstructure and heat treatment on the oxidation rate of both types of coatings. Furthermore, micro hardness, nano hardness and dynamic mechanical analysis (DMA) with a 3-point bend clamp were used in order to study the hardness and Young’s modulus of as-sprayed and annealed HVOF and VPS coatings. The Eshelby inclusion model and image analyses were used in order to further investigate the effect of microstructure on the mechanical properties of these coatings.